Policies and practices of transition towards climate-neutral and smart cities - Gaglione, Federica (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is a continuous update about emerging topics concerning relationships among urban planning, mobility, and environment, thanks to a collection of short scientific papers written by young researchers. The Review Notes are made up of five parts. Each section examines a specific aspect of the broader information storage within the main interests of the TeMA Journal. In particular: the Town Planning International Rules and Legislation. Section aims at presenting the latest updates in the territorial and urban legislative sphere. The current challenges of the city can be enclosed under a single umbrella called “Smart city” which can be a useful approach to define new forms of organizing the complexity of urban life and in turn implement solutions in urban areas ranging from energy consumption to climate change to achieve environmental sustainability goals. In this direction, this review focuses on the involvement of local authorities in the development of urban strategies that focus on smart city objectives within of the Europe2020 strategy and the climate neutral & smart cities mission.